Synergistic effects of surfactants mixture for foam stability measurements for enhanced oil recovery applications - Mumtaz, M. (Society of Petroleum Engineers, 2015)
A protocol is established in order to formulate a surfactant recipe suitable for stable foam generation aimed at foam assisted enhanced oil recovery. Mixture design DoE (Design of Experiment) is employed to develop best performing foaming formulations both in the presence and absence of oil at 90Â°C. Anionic surfactants, alpha olefin sulfonate (AOS) and internal olefin sulfonate (IOS) were blended with zwitterionic surfactant Betadet-S20 (Betaine; foam booster) by using DoE mixture design. The synergism among surfactants structures and mixed surfactants (binary and tertiary) system were evaluated by noting the foam height and endurance. The data were fitted into the cubic model and multiple regression analysis resulted in a third degree polynomial equation. Response surfaces were obtained and analyzed to find the best formulations. The synergistic effect were then correlated and validated against experimentally determined interfacial tension and viscosity of best foaming recipes. The binary formulations of anionic surfactants and betaine were superior for both foam ability and foam stability performance. Surfactant alone on its own and binary system of anionic mixtures were found less stable. The betaine alone was found effective for foam height but was poor for foam endurance. However, anionic surfactants mixed with betaine were found to possess strong interaction and a profound synergistic effect was noted. Reduced amount of anionic surfactant with betaine increased the viscosity of the mixture and produced stronger foam. However, a higher ratio of anionic surfactant decrease the viscosity and generate weaker foam. The use of DoE mixture analysis approach is beneficial for optimum design of foam assisted enhanced oil recovery. Copyright 2015, Society of Petroleum Engineers.